Co-Immobilized Beta-Galactosidase and Saccharomyces Cerevisiae Cells for the Simultaneous Synthesis and Purification of Galacto-Oligosaccharides - Vera-Vera, C (ELSEVIER SCIENCE INC, 2018)
Simultaneous synthesis and purification (SSP) of galacto-oligosaccharides (GOS) from lactose was conducted using a combi-biocatalyst formed by crosslinked enzyme aggregates of Aspergillus oryzae beta-galactosidase and Saccharomyces cerevisiae cells co-immobilized by entrapment in calcium alginate gel particles. Product yield obtained with the combi-biocatalyst was similar than obtained with the soluble enzyme (23.3%), having a final purity of 25.7%. During the simultaneous process, ethyl-beta-galactoside was produced from the ethanol generated as a metabolic product of yeast cells, but ethyl-beta-galactoside was considerably decreased at high aeration (4 vvm). The combi-biocatalyst can be recovered and reused but its performance is limited by the reduction of the metabolic capacity of the cells. In this way, a process was developed for the SSP of GOS from lactose, obtaining a comparable product yield and higher specific productivity than in a conventional synthesis.